Involvement of both cellulose fibrils and a Ca2+-dependent adhesin in the attachment of Rhizobium leguminosarum to pea root hair tips. - Smit, G (1987)
We have previously described an assay for the attachment of Rhizobium bacteria to pea root hair tips (cap formation) which was used as a model to study the attachment step in the nodulation process. Under all conditions tested, a positive correlation was observed between the percentage of fibrillated cells and the ability of these bacteria to form caps and to adhere to glass, suggesting that fibrils play a role in the attachment of Rhizobium leguminosarum to pea root hair tips and to glass (G. Smit, J. W. Kijne, and B. J. J. Lugtenberg, J. Bacteriol. 168:821-827, 1986). In the present paper the chemical and functional characterization of the fibrils of R. leguminosarum is described. Characterization of purified fibrils by infrared spectroscopy and cellulase treatment followed by thin-layer chromatography showed that the fibrils are composed of cellulose. Purified cellulose fibrils, as well as commercial cellulose, inhibited cap formation when present during the attachment assay. Incubation of the bacteria with purified cellulase just before the attachment assay strongly inhibited cap formation, indicating that the fibrils are directly involved in the attachment process. Tn5-induced fibril-overproducing mutants showed a greatly increased ability to form caps, whereas Tn5-induced fibril-negative mutants lost this ability. None of these Tn5 insertions appeared to be located on the Sym plasmid. Both types of mutants showed normal nodulation properties, indicating that cellulose fibrils are not a prerequisite for successful nodulation under the conditions used. The ability of the fibril-negative mutants to attach to glass was not affected by the mutations, indicating that attachment to pea root hair tips and attachment to glass are (partly) based on different mechanisms. However, growth of the rhizobia under low Ca2+ conditions strongly reduced attachment to glass and also prevented cap formation, although it had no negative effect on fibril synthesis. This phenomenon was found for several Rhizobium spp. It was concluded that both cellulose fibrils and a Ca2+ -dependent adhesin(s) are involved in the attachment of R. leguminosarum to pea root hair tips. A model cap formation as a two-step process is discussed.